The impact of work-life balance and organisational commitment on turnover intention among generation Y employees in Malaysian IT and communication sector. - Chong, Hoon Kei; Khor, Yin Jie; Vithya, Nareandran (2021)
The purpose of this study is to study the impact of work-life balance and organisational commitment on turnover intention among Generation Y employees in Malaysian IT and communication sector. The hypothesis of this study is there is a significant relationship between work-life balance, organisational commitment and turnover intention. This study has utilised quantitative, cross-sectional and correlational research design. A total number of one hundred and forty-seven (n=147) Generation Y employees (aged between 20 to 40) who work in the IT and communication sector in Klang Valley, Malaysia were recruited via purposive and snowball sampling methods. The data for this study was gathered through an online survey. The variables of the study were measured by Work-Life Balance Inventory, Organizational Commitment Scale, and Turnover Intention Scale (TIS-6). The study used Pearson Product-Moment Correlation and Multiple Regression Analysis test to test the hypothesis. The result of this study revealed that work-life balance and turnover intention have a significant relationship among Generation Y employees in the Malaysian IT and communication sector. Besides, organisational commitment was found to have a significant negative relationship with turnover intention. Lastly, both work-life balance and organisational commitment were significantly predicted turnover intention; however, organisational commitment has a higher impact than work-life balance on turnover intention among Generation Y employees in the Malaysian IT and communication sector. The findings above contribute to further understanding of these variables for future researchers and provide insights for the organisations especially the human resource department to retain their employees.